MORAL, POLITICS AND METHOD: THE INFLUENCE OF RONALD DWORKIN´S PHILOSOPHY ON THE BRAZILIAN SUPREME COURT - Del Monaco, Luciano; López, Nuria (PANORAMA OF BRAZILIAN LAW, 2014)
This article analyses the use of Ronald Dworkin’s philosophy by the Brazilian Supreme Court. After the Constitution of 1988, the Supreme Court gained a new and broader role in Brazilian political scene. At this time, the work of Ronald Dworkin (and its Brazilian editions) became popular and served as justification for four of the most important cases on the Supreme Court: the fidelity of Congresist’s members on their Political Party; the permission of embryonic stem cells research; the unconstitutionality of press regulation; and the homosexual civil union. Dworkin’s philosophy is a part of the changing-role of the Supreme Court in Brazil. This article offers a demonstration of the use of this philosopher in this in-progress process.